2011
DOI: 10.1088/0004-637x/728/2/142
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Spherical, Time-Dependent Viscous Accretion Flow: One-Dimensional Results

Abstract: We investigated the instability of advective accretion flow as a consequence of angular momentum transfer in one-dimensional, quasi-spherical transonic accretion flow around a non-rotating black hole. The code is designed to include the effects of viscosity; the hydrodynamics component preserves angular momentum strictly with Lagrangian and remap method in absence of viscosity, while the viscosity component updates viscous angular momentum transfer through the implicit method. We performed two tests to demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 57%
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 57%
“…In realistic disc, both processes are active, and both should produce shock oscillation. Interestingly though, viscosity can produce multiple shocks (for one spatial dimensional results see Lee et al 2011), while no such thing has been reported with cooling processes, albeit investigations with cooling processes have not been done extensively. We would like to investigate the combined effect of cooling and viscous dissipation in future, to ascertain the viability of 'shock cascade' in much greater detail.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…We would like to find the condition of the shocked disc that produces weak or strong jets. Disc instability due to viscous transport has been shown before and has been identified with QPOs (Lanzafame et al 1998(Lanzafame et al , 2008Lee et al 2011), however, we would like to show how this instability might affect the shock induced bipolar outflows. Moreover, it has been shown theoretically that the energy and angular momentum for which steady shock exists in inviscid flow, will become unstable for viscous flow (Chakrabarti & Das 2004;.…”
Section: Introductionmentioning
confidence: 87%
“…This difference induces major changes in the Rankine-Hugoniot conditions, though, some of their conclusions remain similar to those present in our work. In Lanzafame et al (1998) and Lee et al (2011) shocks move outward with increasing α as in our present paper where we kept the conditions on the horizon and inner sonic points fixed.…”
Section: Discussionmentioning
confidence: 89%